Serious Game for Teaching Undergraduate Medical Students in Cleft lip and Palate Treatment Protocol. (September 2020) - Palee, Patison; Wongta, Noppon; Khwanngern, Krit; Jitmun, Waritsara; Choosri, Noppon
Highlights: Sharing the practice and experience of implementing a serious game for teaching Cleft Lip/Palate treatment protocol to undergraduate medical students. Multiple assessment techniques applied to measure the performance of the game. The developed game shows promising results to be used as a supplementary learning material in a medical school setting. Abstract: Objectives: To develop and evaluate a serious game to deliver knowledge about the cleft lip with or without cleft palate (CL/P) protocol used in Craniofacial Center, Chiang Mai University. Methods: The game "Cleft Island" was developed then extensively evaluated using different criteria, including the measured knowledge gained by participants, and gameplay experience. A group of 53 fourth and fifth-year medical students (male: 24, female: 29) were recruited to take part in an experiment. They were from the Faculty of Medicine, Chiang Mai University, and had just rotated to the Department of Surgery. Three evaluations were conducted: 1) to test whether the players had competently gained CL/P knowledge; 2) to evaluate the usability of the game according to the System Usability Scale (SUS); and 3) to evaluate the game experience in terms of a Game Experience Questionnaire (GEQ) test. Results: The results indicate a statistically significant improvement of medical students' knowledge after performing the Wilcoxon Signed-Ranks test (p < 0.5) between pre-test and post-test scores of the same medical student group; the acceptable average SUS score (M = 55.28) of the serious game; a moderate degree of experience of the GEQ components including positive affect (M = 2.64), competence (M = 2.49), and immersion (M = 2.21). Conclusions: Cleft Island can be used as an effective supplementary instructional material, which has the potential to provide significant knowledge of CL/P treatment protocol for the players. As far as the authors are aware, this is the first study to implement and assess a serious game for training in CL/P protocol.